Content of total and easy soluble cobalt in the vertisols of Kratovo-Zletovo volcanic region - Gjorgjiev, Mitko; Petkovski, Dime (Macedonian Journal of Ecology and Environment, 1994)
The paper represents the investigations on total and easy soluble cobalt content in the vertisols of Kratovo-Zletovo volcanic region. The content of the total cobalt is 3,00 to 18,00 ppm. The soils of profile 734 and 720 have the highest content of total cobalt, while of profile 15,727 and 7 have the lowest one. The contents of an easily soluble and total Co and pH, and the content of carbonates direct relation is not noticed.